أثر استراتيجية تعليم الأقران في تنمية مهارات فهم المقروء لدى الطلاب قسم الإعداد اللغوي بجامعة الراية - Ridwan Syahrun J.B Usman (Rayah Al-Islam, 2018)
The approach taken to reach the target in this study was the experimental approach because the subject needed an experiment in the field to find the results. The research sample consisted of (20) students from STIBA Ar Rayah, divided into two groups: the first was an experimental group consisting of (10) students and other officers (10) students. The results showed a positive impact from using peer tutoring education strategies in developing reading comprehension skills for students at STIBA Ar Rayah with the following results: 1) This study achieves a list of skills in reading comprehension and it is contained in five levels and the number of skills of all levels is fifteen skills. 2) This research has shown that teaching using the peer education strategy has influenced development of skills to understand reading results for students from STIBA Ar Rayah. 3) This research has also proven that the use of peer education strategies is more effective than direct teaching in developing reading comprehension skills from STIBA students Ar Rayah.